2021
DOI: 10.3759/tropics.ms20-03
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal changes in biomass after selective logging in a lowland tropical rainforest in Peninsular Malaysia

Abstract: We studied biomass changes in a lowland tropical rain forest in the Pasoh Forest Reserve of Peninsular Malaysia after selective logging in 1958. A tree census was undertaken every 2 years from 1998 to 2012 in a 6-ha logged forest plot. Total aboveground biomass (AGB) was 72 % of that in a primary forest plot within the same reserve in 1998, but reached 87 % in 2012. AGB regrowth was spatially variable within the logged forest plot and was much less in swampy areas than in upland areas. The overall annual growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The estimated total AGB in 2017 in the comparable (conventional) method was 475.8 Mg ha −1 , which was far higher than that in the previous report, which indicated that AGB increased at by an average of 2.3 Mg ha −1 per year in 1998-2017. The total AGB of tropical forests generally highly fluctuated with time, as well as space (Okuda et al 2021). In particular, because the plot included a 'disturbed area' in the past; these areas would have recovered in more recent years and contributed to increased AGB, which was also suggested in the former study (Okuda et al 2021).…”
Section: Agb Estimationmentioning
confidence: 65%
See 2 more Smart Citations
“…The estimated total AGB in 2017 in the comparable (conventional) method was 475.8 Mg ha −1 , which was far higher than that in the previous report, which indicated that AGB increased at by an average of 2.3 Mg ha −1 per year in 1998-2017. The total AGB of tropical forests generally highly fluctuated with time, as well as space (Okuda et al 2021). In particular, because the plot included a 'disturbed area' in the past; these areas would have recovered in more recent years and contributed to increased AGB, which was also suggested in the former study (Okuda et al 2021).…”
Section: Agb Estimationmentioning
confidence: 65%
“…The total AGB of tropical forests generally highly fluctuated with time, as well as space (Okuda et al 2021). In particular, because the plot included a 'disturbed area' in the past; these areas would have recovered in more recent years and contributed to increased AGB, which was also suggested in the former study (Okuda et al 2021).…”
Section: Agb Estimationmentioning
confidence: 65%
See 1 more Smart Citation
“…As is known, the rate of chemical reactions doubles when the temperature is increased by 10 • C (Van 't Hoff reaction). When cutting down a stand, it is possible to change the thermal regime of soils due to the "opening" of the territory from the forest canopy, which can directly and indirectly enhance the microbial transformation of organic matter [15,20]. In this regard, a question also arises regarding the need to optimize the state of the microbiota so that carbon losses into the atmosphere are optimal and the forest can perform its ecosystem functions of maintaining the carbon balance in the ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in ecosystem processes lead to changes in the type of vegetation, carbon recycling in the plant-soil system, microbial transformation of organic matter and patterns of biomass distribution [14,19,20]. There may also be spatial-temporal changes in biomass, tree composition and diversity in the forest [12,20,21]. A change in soil organic matter may indirectly affect global climate warming [22].…”
Section: Introductionmentioning
confidence: 99%